Big Data-Driven Risk Analysis of Environmental Grievances in the Palm Oil Industry for Sustainable Decision-Making - Idris, Muhammad Syahmi; Md Nor, Muhamad Shahrul; Ali, Syazwani; Mat Ali, Norazman; Yoong, Siew Wai; Mohd Nor, Mohd Nazli; Mohd Muhili, Mohd Suffian; Noor Hassim, Muhamad Fairus (Institut Pertanian Bogor (IPB University), 2025)
The expansion of the palm oil industry affects environmental sustainability. This study aims to assess palm oil's environmental grievances reported pre- and post-Covid-19. A hybrid of data-driven and multicriteria decision-making analyses was used to analyze unstructured data from nine companies' grievance logs. A total of 884 cases with the trend peaking in 2019. Predominantly deforestation, a total of 564 cases affecting 66,716.23 ha in Indonesia, 312 cases affecting 49,704.97 ha in Malaysia, 6 cases affecting 43,500 ha in Papua New Guinea, and 2 cases in the Philippines. Network analysis reveals that the environmental grievances affected multiple companies, with WILMAR suppliers at the center. On average, companies take 100 days to resolve. Clustering analysis shows Sime Darby Oil, WILMAR, KLK, and Mewah Group have influences on addressing grievances in high-risk provinces. Quantile-quadrant analysis reveals that provinces in Kalimantan, Pahang, and Sarawak are in the high-risk quadrant and therefore require immediate mitigation plans. This finding points toward the need for the formation of a private consortium among identified key players and local government in the high-risk region as a new strategy to improve management of environmental sustainability issues that predominantly involve deforestation.